Some Comments About the Cultural-Historical Scientific School - Ahmedov Hoshim Hakimovich (Peerian Journals Publishing, 2022)
This article analyses the theoretical conclusions of the representatives of the School of Culture and History, which appeared in the XIX century. Theories of the school's scientific approach to art, history, and literature are discussed. Important aspects will be highlighted. The significance of their conclusions about the essence of fiction is analyzed.
Keywords: : Cultural-historical school; Ten; opinions of Uzbek literary critics; art and literature